High‐Performance Work Systems in Professional Service Firms: Examining the Practices‐Resources‐Uses‐Performance Linkage. Issue 2 (9th December 2015) - Fu, Na; Flood, Patrick C.; Bosak, Janine; Rousseau, Denise M.; Morris, Tim; O'Regan, Philip
Abstract: Professional service firms (PSFs) play an important role in the knowledge‐based economy. Their success is highly dependent on their people, the knowledge resources they possess, and how they use these resources. However, how to systematically manage human resources to attain high performance is not fully understood. This study addresses this issue by investigating the linkage mechanisms through which high‐performance work systems (HPWS) influence the performance of PSFs. We integrate resource‐based and dynamic capability theories in order to identify and investigate two intervening mechanisms that link HR practices to firm performance. The first mechanism is the intellectual capital resources comprising the human, social, and organizational capital that HPWS create. The second mechanism is the uses to which both HPWS and resources can be applied, operationalized as organizational ambidexterity, the simultaneous exploitation of existing knowledge and exploration of new knowledge. These mechanisms are hypothesized to link HPWS to firm performance in the form of a practices‐resources‐uses‐performance linkage model. Results from a longitudinal study of 93 accounting firms support this linkage model. © 2015 Wiley Periodicals, Inc.